Answer:
x = ±√37/9
Step-by-step explanation:
x² = 37/81
√(x²) = √(37/81)
x = ± √(37)/√(81)
x = ± √37/9
Answer:
B(-2, -7)
Step-by-step explanation:
Midpoint is (0, -3)
A(x₁, y₁) B(x₂, y₂)
A(2, 1)
![Midpoint = (\frac{x_{1} + x_{2} }{2}, \frac{y_{1} + y_{2} }{2} )\\\\Midpoint = (\frac{2+ x_{2} }{2}, \frac{1 + y_{2} }{2} )](https://tex.z-dn.net/?f=Midpoint%20%3D%20%28%5Cfrac%7Bx_%7B1%7D%20%2B%20x_%7B2%7D%20%7D%7B2%7D%2C%20%5Cfrac%7By_%7B1%7D%20%2B%20y_%7B2%7D%20%7D%7B2%7D%20%29%5C%5C%5C%5CMidpoint%20%3D%20%28%5Cfrac%7B2%2B%20x_%7B2%7D%20%7D%7B2%7D%2C%20%5Cfrac%7B1%20%2B%20y_%7B2%7D%20%7D%7B2%7D%20%29)
![(0, -3) = (\frac{2+ x_{2} }{2}, \frac{1 + y_{2} }{2} )](https://tex.z-dn.net/?f=%280%2C%20-3%29%20%3D%20%28%5Cfrac%7B2%2B%20x_%7B2%7D%20%7D%7B2%7D%2C%20%5Cfrac%7B1%20%2B%20y_%7B2%7D%20%7D%7B2%7D%20%29)
![\frac{2+ x_{2} }{2} = 0\\\\2 + x_{2} = 0\ \ \ \ times\ both\ sides\ by\ 2\\x_{2} = -2\ \ \ \ subtract\ both\ sides\ by\ 2](https://tex.z-dn.net/?f=%5Cfrac%7B2%2B%20x_%7B2%7D%20%7D%7B2%7D%20%3D%200%5C%5C%5C%5C2%20%2B%20x_%7B2%7D%20%3D%200%5C%20%5C%20%5C%20%5C%20times%5C%20both%5C%20sides%5C%20by%5C%202%5C%5Cx_%7B2%7D%20%3D%20-2%5C%20%5C%20%5C%20%5C%20subtract%5C%20both%5C%20sides%5C%20by%5C%202)
![\frac{1 + y_{2} }{2} = -3\\\\1 + y_{2} = -6\ \ \ \ times\ both\ sides\ by\ 2\\y_{2} = -7\ \ \ \ subtract\ both\ sides\ by\ 1](https://tex.z-dn.net/?f=%5Cfrac%7B1%20%2B%20y_%7B2%7D%20%7D%7B2%7D%20%3D%20-3%5C%5C%5C%5C1%20%2B%20y_%7B2%7D%20%3D%20-6%5C%20%5C%20%5C%20%5C%20times%5C%20both%5C%20sides%5C%20by%5C%202%5C%5Cy_%7B2%7D%20%3D%20-7%5C%20%5C%20%5C%20%5C%20subtract%5C%20both%5C%20sides%5C%20by%5C%201)
∴ B(-2, -7)
Answer:
x = -4
Step-by-step explanation:
Step 1: Define
j(x) = 3x + 1
j(x) = -11
Step 2: Substitute and solve for <em>x</em>
-11 = 3x + 1
-12 = 3x
x = -4
We use BEDMAS and we go from left to right
Therefore; 1. 9+34 = 43
2. 43+5452 = 5495
3. 5495 -49349 = -43854
4. -43854+4 = -43850
Final Answer is - 43' 850.